tert -Butyl 4-({[( E )-1,3-dimethyl-5-phenoxypyrazol-4-yl]methyl}aminooxymethyl)benzoate - Fu, Na; Zou, Xiao-Mao; Lin, Da-Yong; Zhu, You-Quan; Yang, Hua-Zheng (Acta crystallographica. Section E, Structure reports online, 2008)
The title compound, C24H27N3O4, also known as fenpyroximate, is a commercial acaricide. The benzene ring of the phenoxy group is approximately perpendicular to the pyrazole ring with a dihedral angle of 84.37 (11)°. The dihedral angle between the phenoxy and the benzoate benzene rings is 48.83 (8)°.